2014
DOI: 10.18632/oncotarget.2528
|View full text |Cite
|
Sign up to set email alerts
|

The induction of the p53 tumor suppressor protein bridges the apoptotic and autophagic signaling pathways to regulate cell death in prostate cancer cells

Abstract: The p53 tumor suppressor protein plays a crucial role in influencing cell fate decisions in response to cellular stress. As p53 elicits cell cycle arrest, senescence or apoptosis, the integrity of the p53 pathway is considered a key determinant of anti-tumor responses. p53 can also promote autophagy, however the role of p53-dependent autophagy in chemosensitivity is poorly understood. VMY-1-103 (VMY), a dansylated analog of purvalanol B, displays rapid and potent anti-tumor activities, however the pathways by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 52 publications
1
48
0
Order By: Relevance
“…For instance, atorvastatin is considered by some to cause autophagy to promote apoptosis in human prostate cancer cells (33), whilst others have a contrasting views, and consider that inhibition of autophagy potentiates atorvastatin-induced apoptotic cell death (34). Although there is known crosstalk between autophagy and apoptosis, since they share certain signaling pathways and proteins, the mechanism where this bridging occurs has not been fully defined (35). In the present study autophagy was induced by rottlerin, as indicated by a number of observations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, atorvastatin is considered by some to cause autophagy to promote apoptosis in human prostate cancer cells (33), whilst others have a contrasting views, and consider that inhibition of autophagy potentiates atorvastatin-induced apoptotic cell death (34). Although there is known crosstalk between autophagy and apoptosis, since they share certain signaling pathways and proteins, the mechanism where this bridging occurs has not been fully defined (35). In the present study autophagy was induced by rottlerin, as indicated by a number of observations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, fangchinoline induces autophagic cell death through the p53/Sestrin2/AMPK signaling in PLC/PRF/5 and HepG2 cells . VMY‐1‐103 is a dansylated analog of purvalanol B and is also reported to have a remarkable antitumor activity through p53‐dependent autophagy in prostate cancer cells . Paclitaxel triggers autophagic cell death with increased p53 expression before LC3B regulation in various cancers, such as glioma, colon cancer, and prostate cancer cells …”
Section: Autophagic Cell Death and Small‐molecule Compounds In Cancermentioning
confidence: 99%
“…For example, reformulated differentiation medias that may better promote luminal vs basal differentiation can be rapidly tested. Since lentiviral infection of CRCs has been performed as easily as with commercial cancer cells 7 and the 2D CRCs have also been transfected with CAS9/CRISPR gene editing technology vectors to permanently modify the cell genome (data not shown), the effect of mutated, deleted or repaired genes can be tested. Similarly, lineage tracking can be made possible by introducing lineage specific reporter genes.…”
Section: Discussionmentioning
confidence: 99%
“…Note: CM is F-media conditioned by irradiated J2 cells and contains 10 μm Y-27632 as previously described 7,8,9,11 .…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation